PENGEMBANGAN METODOLOGI PENGAJARAN DAN KOMPETENSI KEPRIBADIAN DOSEN BAHASA ARAB - Faisal Hendra (Arabi : Journal of Arabic Studies, 2021)
This article discusses the development of lecturer competencies in using methods and techniques in learning Arabic language proficiency in Indonesian universities. This study uses a descriptive evaluative approach to the data obtained at the Arabic Language and Culture Study Program, Universitas Al Azhar Indonesia (UAI). From the study conducted, it was found that one of the reasons for the not yet maximal ability of students in mastering Arabic language proficiency in Indonesian universities, especially at UAI, was because the lecturers who taught were not maximal in using teaching methodologies and techniques. The technique used is not innovative and tends to be repetitive and boring so that students are not maximally motivated to learn Arabic. Some tips that can be done in instilling a sense of love between lecturers and students in learning and good relations between lecturers and student families can affect the success of the Arabic language learning process that can be implemented.